Self-Disclosure and Anxiety in University Students in Long-Distance Relationships: An Attachment Style Perspective - Sekar Pudjiastuti; Fikrotul Hanifah (Riviera Publishing, 2025)
Long-distance relationships are a condition frequently experienced by university students in romantic partnerships, often leading to anxiety due to the limited opportunities for direct interaction. This research aims to examine the effect of self-disclosure on the anxiety of students engaged in long-distance relationships, viewed from the perspective of attachment style. The research employed a quantitative approach with 265 participants selected through purposive sampling. Three instruments were used for measurement: the Zung Self-Rating Anxiety Scale (ZSAS), a self-disclosure scale based on Devito’s (1986) theory, and an attachment style scale adapted from Bartholomew and Horowitz (1991). Data were analyzed using moderated multiple linear regression. The findings revealed a significant effect of self-disclosure on student anxiety; however, attachment style did not strengthen or weaken this effect. This study provides practical implications for students in maintaining long-distance relationships through enhanced self-disclosure, as well as theoretical contributions to the field of relationship psychology. Self-disclosure is effective in reducing student anxiety in LDR, but its effectiveness is not affected by attachment styles. These findings provide practical implications for students in managing LDR through increased openness, as well as theoretical contributions to the development of relationship psychology.